Management of Hepatitis B Virus Reactivation after the Completion of Cancer Chemotherapy using a Plan-do-Check-Act Cycle (Journal of Cancer Research Updates, 2022)
The reactivation of the hepatitis B virus (HBV) following systemic chemotherapy reportedly caused acute liver dysfunction as a fatal complication. HBV reactivation sometimes occurs even after the cessation of chemotherapy, especially in the patients with hematological malignancies. A retrospective survey of patients with hepatitis B surface (HBs) antigen-negative cancer with HBs and/or HBc antibodies was conducted by a multidisciplinary chemotherapy team to determine the examination rate of the HBV DNA test after the completion of chemotherapy. Among 83 patients with a resolved HBV infection, who were followed up for more than 3 months, only 17 patients underwent HBV DNA monitoring every 1-3 months (17/83; 20.5%). Since September, 2022, the chemotherapy team has informed the attending physician regarding the continuous HBV DNA monitoring in patients with cancer with a resolved HBV infection until 12 months after the cessation of chemotherapy.